2016
DOI: 10.1542/peds.2015-3013
|View full text |Cite
|
Sign up to set email alerts
|

A Parent Coach Model for Well-Child Care Among Low-Income Children: A Randomized Controlled Trial

Abstract: OBJECTIVE: The goal of this study was to examine the effects of a new model for well-child care (WCC), the Parent-focused Redesign for Encounters, Newborns to Toddlers (PARENT), on WCC quality and health care utilization among low-income families. METHODS:PARENT includes 4 elements designed by using a stakeholder-engaged process:(1) a parent coach (ie, health educator) to provide anticipatory guidance, psychosocial screening and referral, and developmental/behavioral guidance and screening at each wellvisit; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 42 publications
1
65
0
Order By: Relevance
“…We explored receptiveness to health care delivery innovations that have been suggested to reduce use of the ED in other patient populations . First, we asked caretakers’ opinion on the use of CHWs to inform the treatment of their child's low‐acuity illnesses and allowed them to define how a CHW might be useful.…”
Section: Resultsmentioning
confidence: 99%
“…We explored receptiveness to health care delivery innovations that have been suggested to reduce use of the ED in other patient populations . First, we asked caretakers’ opinion on the use of CHWs to inform the treatment of their child's low‐acuity illnesses and allowed them to define how a CHW might be useful.…”
Section: Resultsmentioning
confidence: 99%
“…As this paper focuses on parent experiences with the intervention, we do not present control group data; an intervention versus control group analysis is presented elsewhere. 20 Social desirability bias may also limit our findings; to reduce this type of bias, all quantitative and qualitative surveys were conducted privately with a research assistant who was not directly involved in the intervention and not affiliated with the pediatric practices. Additionally, the intervention experiences of participants were highly influenced by the PC.…”
Section: Discussionmentioning
confidence: 99%
“…In this survey, we collected data on outcome measures on receipt of WCC services to compare intervention and control participants; these outcome measures for intervention vs. control parents are reported elsewhere. 20 The survey also included a series of questions for all intervention parents to assess their experience with the intervention. These survey questions asked intervention participants about each PARENT component, whether they utilized the specific components, how often they used it, its helpfulness to them, and whether they would recommend it to others (Appendix A).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent randomized controlled trial of 251 families, this intervention showed significant improvements in the receipt of WCC services and experiences of care, as well as a reduction in emergency department visits. 54 …”
Section: Care Coordination Programsmentioning
confidence: 99%